IMPLICATIONS OF USING SHADING MESHES AND PLANT DENSITY ON THE LEAF ANATOMY OF Corymbia citriodora (Hook.) K.D. Hill & L.A.S. Johnson SEEDLINGS - Claiton Nardini; João Antônio de Cristo; Braulio Otomar Caron; Gabrieli Cristina Vitalli de Azevedo; Matheus Milani Pretto; Erick dos Santos Silva; Jaqueline Sgarbossa; Elder Eloy; Denise Schmidt (Revista Árvore)
ABSTRACT Shading meshes are important techniques used during seedling cultivation. However, improper use can lead to excessive shading, which may be intensified by the distribution of seedlings in the tray, directly affecting their growth and development. This study aimed to assess the effect of using colored shading meshes combined with different plant densities on the leaf anatomy and seedling quality of Corymbia citriodora (Hook.) K.D. Hill and L.A.S. Johnson. The experiment was conducted in a protected environment at the Federal University of Santa Maria Frederico Westphalen campus, from May to September 2018. A completely randomized experimental design was used, in a 2 x 3 factorial scheme with two seedling densities, two shading meshes, and no mesh. The assessed densities consisted of 736 seedlings per m2 (high density) and 528 seedlings per m2 (medium density). The shading meshes used were in the red and blue colors, and there was a meshless (full sun) treatment as well. Assessments were conducted when seedlings reached 25 cm in height, with the following variables being analyzed: stomatal count, cuticle thickness, adaxial and abaxial epidermis thickness, spongy and palisade parenchyma thickness, as well as seedling quality through the Dickson Quality Index. The use of meshes in different colors and the plant densities altered the anatomical characteristics of Corymbia citriodora, such as cuticle and adaxial epidermis thickness, abaxial epidermis, palisade parenchyma, and leaf thickness. However, these anatomical changes observed in seedlings under different meshes do not necessarily indicate better seedling quality.